1994
DOI: 10.1159/000098630
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation in Low Back and Leg Pain

Abstract: We have reviewed our experience with spinal cord stimulation (SCS) in patients with low back and leg pain. 33 patients complaining of leg and low back pain underwent percutaneous tests of SCS. 28 patients had failed back surgery syndromes, 1 patient had pain related to an L1 vertebral body fracture, another from Tarlow cysts and the remaining 3 patients had lumbosacral spondyloarthrosis and osteoporosis without radiological signs of root compression. 28 patients showed mono- or pluriradicular deficits. At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 0 publications
0
20
1
4
Order By: Relevance
“…Spinal cord stimulation (SCS) is a safe, reversible, and efficacious treatment option for select patients with medically intractable chronic pain syndromes such as failed back surgery syndrome (FBSS) and complex regional pain syndrome (CRPS) (1–13). SCS systems are routinely implanted after a trial with percutaneous leads.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord stimulation (SCS) is a safe, reversible, and efficacious treatment option for select patients with medically intractable chronic pain syndromes such as failed back surgery syndrome (FBSS) and complex regional pain syndrome (CRPS) (1–13). SCS systems are routinely implanted after a trial with percutaneous leads.…”
Section: Introductionmentioning
confidence: 99%
“…Patients diagnosed with CRPS, FBSS (Figures 4 and 5), and PHN have shown significant success rates in pain management and cost-effectiveness associated with low rates of complications. The total pain management was rarely obtained by the use of SCS as therapy as indicated in Tables 2-4 (22,38,39,41,50,58,60,(65)(66)(67).…”
Section: Results In Pain Managementmentioning
confidence: 99%
“…Meglio et al [5] reported on their experience with 33 patients with leg and back pain. Most of these patients (28) had FBSS, and all were evaluated with a trial of percutaneous electrode stimulation.…”
Section: Recent Studiesmentioning
confidence: 99%